Social Emotions Skills: Analisis Intensitas Penggunaan Media Sosial Terhadap Self Awareness Abilities Pada Remaja - Ilsya Mulya Insani,; Sofy Sukmawati,; Mina Holilah,; Retno Ayu Hardiyanti, (The Indonesian Journal of Social Studies, 2023)
The use of social media greatly influences individual self-awareness with the surrounding environment. When teenagers access social media with high intensity, indirect interactions will result in less direct social interaction and low sensitivity to the environment. This can be influenced because self-awareness in individuals is low. This study aims to find out about the intensity of social media use on self-awareness in adolescents at SMPN 29 Bandung. Based on the results of the interviews we conducted, these teenagers used social media quite often, but they rarely made their daily statuses or updates on their personal social media accounts, especially boys, and for female students, they preferred to update their daily lives through second accounts. These teenagers will stop using social media when their cell phones are being charged and when they feel tired. However, this only lasts for a while after their cellphone battery is charged, they will play cellphones again. Because some of the hobbies they like are still related to mobile phones such as playing online games, listening to music, or watching movies, things like this reduce the intensity of direct social interaction. With this, it means that low self-awareness behavior is related to the high intensity of social media use in adolescents.